Potential of solar energy harvesting in Ulu Pauh, Perlis, Malaysia using solar radiation - Analysis studies - Noor Syafawati, Ahmad; Ismail, Daut, Prof. Dr.; Muhammad Irwanto, Misrun; Farhana, Z.; Nurul Razliana, Abd Razak; Arizadayana, Zahalan; Saidatul Shema, Saad (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/